إدارة الأزمات من منظور السياسة الشرعية - Taghreed Yaaqub Abu Sbaih (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
The concept of crisis management has become one common terminology in various fields, especially in shariah science. This study, the presentation of this confrontation and how it confronts a global disease crisis known as the Corona "Covid-19 crisis". It demonstrates the practical and applied aspect of managing this crisis through the preventive and therapeutic aspects. It aims also to get out of it with the least losses possibility within the controls of Islamic law to fulfil the individual and the collective interests to preserve the necessities that must be preserved. The study reached several conclusions, including our prophets (peace be upon him) skill, and his companions (may Allah be pleased with them). In managing many of the crises they were subjected to. To show also that this knowledge was known to them even though not in its modern terms. As that the Glorious Sharia realizes through its faculties every crisis that arises in the Islamic Nation and finds out the legitimate solutions for it.